The Effectiveness of 3d Hologram Media on Elementary School Students' Learning Outcomes in Natural and Social Sciences (IPAS) Subjects - Ade Vidianti; Johan Eka Wijaya DN; Anita Adesti; Yelmi Yunarti; Aprilia Yustika Dewi; Ade Dwi Jayanti (EDUJAVARE: International Journal of Educational Research, 2026)
The rapid development and advancement of educational science in the modern era have significantly influenced the growth of the educational sector worldwide. This study aims to determine the effectiveness of 3D Hologram Media on Elementary School Students' Learning Outcomes in Natural and Social Sciences (IPAS) subjects. This type of research is quantitative with an experimental method. The form of the experimental approach with a research design is One-Group Pretest-Posttest. The research sample is 14 people. Data collection techniques and tools use multiple-choice tests, analysis techniques using the "t" test. The results of the calculation of normally distributed data for posttest data show that L count 0.187 < L table 0.227 and for pretest data it is found that L count 0.114 < L table 0.227. The results of homogeneous calculations obtained a value of 1.409 < 7.879. The results of the calculation and analysis of data from the results of hypothesis testing at a significance level of 5% with df = 13 obtained the price of "t" table which is 1.770. The results of hypothesis testing show that t count > t table which is proven at a level of 5%, namely 13.142 > 1.770. The data shows that (Ha) the alternative hypothesis is accepted, and (H0) the null hypothesis is rejected. Thus, the use of 3D hologram media is effective for student learning.